Development of aggressive-victims from childhood through adolescence: Associations with emotion dysregulation, withdrawn behaviors, moral disengagement, peer rejection, and friendships. (February 2020) - Ettekal, Idean; Ladd, Gary W.
Abstract: At multiple developmental periods spanning from middle childhood through adolescence, we investigated the development of aggressive-victims. Multiple-informant data collected across four grade levels (1, 5, 8, and 11; N = 482; 50% females) was used to perform person-centered analyses including latent profile and latent transition analyses in order to examine the co-occurring development of multiple forms (i.e., physical, verbal, and relational) of aggression and peer victimization. Results indicated that there were two distinct subgroups of aggressive-victims, one of which was more relational in form (i.e., relational aggressive-victims), and children in these two subgroups were distinguishable with respect to their individual characteristics (emotion dysregulation, withdrawn behaviors, and moral disengagement) and relational experiences (peer rejection and friendships). Furthermore, the findings elucidated the mechanisms by which developmental continuity and change (i.e., transitions) among the subgroups occurred across childhood and adolescence.